Fish Diversity, Endemism, Threats, and Conservation in the Jinsha River Basin (Upper Yangtze River), China. (11th June 2020) - Liu, Han; Guo, Chuanbo; Qu, Xiao; Xiong, Fangyuan; Paukert, Craig P.; Chen, Yushun; Su, Wei
Abstract: The Jinsha River, which comprises the upper reaches of the Yangtze River, has among the highest freshwater fish biodiversity and endemism in China, but these characteristics have rarely been quantitatively evaluated at the basin scale. We used fish presence–absence data collected from the entire Jinsha River basin (JRB) from 1964 to 2017 to determine patterns in fish biodiversity. In total, 229 freshwater fish species from 9 orders, 26 families, and 110 genera were recorded. Of these species, 161 were endemic to China, with 94 species being endemic to the Yangtze River basin, and 39 species were threatened. Fish species richness was higher in the downstream river reaches and was higher in the main stem than in the tributaries. Overfishing, water pollution, and dam construction have been threatening fish diversity in the JRB for several decades. Conservation strategies similar to those used in North America may be applicable to the JRB to help protect native fishes in this important river basin. Such strategies include (1) assessment of several tributaries as fish reserves; (2) regular adjustment of turbine operations during the fish spawning period; and (3) regulation of the many co‐occurring human stressors in the JRB.